The Effect of Tera Gymnastics on Reducing Hypertension in the Elderly in Dukugawing-Kepunduan Cirebon - Erna Marissa, Dewi; Fadilah, Erida; Sazilli, Dikha (Jurnal Medisci, 2024)
Elevations in blood pressure and pulse might result from changes in the cardiovascular system that occur with aging, including the loss of artery flexibility. Motion-based exercise for the elderly increases the release of hormones that relax the patient by stimulating the sympathetic and parasympathetic nervous systems. Senior gymnastics is an excellent physical activity for removing fat and cholesterol from blood vessels. This study aimed to determine the impact of senior exercise on hypertension in the older population in the Dukugawing Block, Kepunduan Village, Dukuntang District, and Cirebon Regency. The pre-experimental research design employed in this study included 34 senior hypertensive participants in a one-group pre-posttest design using simple total sampling. As the data were normally distributed, a paired t-test was used for data analysis after blood pressure was taken using a sphygmomanometer and elderly gymnastics was measured using a standard operating procedure (SOP). As a result of the intervention, the average blood pressure dropped from 150/94 mmHg to 140/90 mmHg, according to the data. After administering an aged exercise intervention for the elderly in the Dukugawing Block, Kepunduan Village, Dukuntang District, Cirebon Regency, a paired sample t-test analysis yielded a p-value = 0.00 <0.05, indicating a significant difference in blood pressure before and after participation.